Shio Dalam Tinjauan Values of Children - Ocvitalia, Shally (Universitas Muhammadiyah Jember, 2019)
Every parent in the world will feel many things when having a child. The birth of a child will also make parents have new hopes for themselves, their families and also for the children themselves. Values of Children is one theory that can explain the expectations of parents when having children. This literature research aims to explain the relationship between chinese zodiac and values of children in society. The results of this literature study show there are two values of children towards parents based on a review of values of children. The categories included in social values are, a)Adult status & social identity, b) Achievement, competence, creativity, c)Power, influence, effectiveness and d)Social comparison. Whereas the category included in economic value is economic utility, security in old age. Referring to the results of the literature research, a psychological approach can be applied in developing knowledge, understanding and insight into the relation of chinese zodiac and values of children to society in general. The implications of theory and practice can be discussed further.